International politics : - Schuman, Frederick L. (McGraw-Hill book company, inc., 1958)
Frederick Lewis Schuman was a historian, an American political scientist and international relations scholar. He was a professor of history at Williams College, an analyst of international relations, and social scientist, focusing on the period between World War I and World War II.